ELECTORAL VOLATILITY DALAM PERSPEKTIF KELEMBAGAAN PARTAI POLITIK DI INDONESIA : SEBUAH ANALISIS HUBUNGAN PARTAI POLITIK DENGAN KONSTITUEN - Nasir, Nurlatipah (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2016)
According to Mainwaring, party systems in the third-wave democracies are markedly less institutionalized than those in most long-established democracies, more institutionalized systems are ones in which parties have strong roots in society. After the fall of Soeharto, the political parties in Indonesia facing many problems, especially on the relation between the parties and their constituent. The increasing number of electoral volatility show an instability as caused by the political parties which is weakly institutionalized. Whereas, the institutionalized political parties is generally acknowledged positively correlated with the consolidation of democracy.